Long term variabilities and tendencies of mesospheric lunar semidiurnal tide over Tirunelveli (8.7 deg N, 77.8 deg E) - Sathishkumar, S.; Sridharan, S.; Kutty, P.V. Muhammed; Gurubaran, S. (My University, 2017)
The medium frequency radar deployed at Tirunelveli (8.7 N, 77.8 E), which is located near the southmost tip of peninsular India, have been providing continuous data from the year 1993 to the year 2012 that helped to study the long term tendencies in the lunar tidal variabilities over this geographic location. In the present paper we present the results of seasonal, interannual and long-term variabilities of lunar semi-diurnal tides in the upper mesosphere over Tirunelveli. The present study also includes comparison with model values. The study shows that the tidal amplitudes are larger in the meridional components of the mesospheric winds than the zonal winds. The seasonal variations of the tides are similar in both the components. The tides show maximum amplitudes of about ~5 m/s in February/March, secondary maximum amplitudes of about ~3 m/s in September and minimum amplitudes during summer months (May–August). The observed seasonal variation of the lunar tides do not compare well with Vial and Forbes (1994) model values, though it is consistent with earlier observations. The lunar tidal phase in meridional winds leads that in zonal winds from January to June and from September to November, while the latter leads the former during July/August. The lunar tides show large interannual variability. There are unusual amplitude enhancements in the lunar tide in meridional winds during the winters of 2006 and 2009, when major sudden stratospheric warmings (SSW) occurred at high latitude northern hemisphere, whereas zonal lunar tide does not show any clear association with the SSW. Vertical wavelengths of lunar tides in zonal and meridional wind are in the range of 20–90 km. The vertical wavelengths of lunar tides in both zonal and meridional component are smaller in June and larger in November and December. The monthly mean zonal and meridional winds are subjected to regression analysis to study the tidal response to long-period oscillations, namely, quasi-biennial oscillation (QBO), solar cycle variation and El-nino southern oscillation (ENSO). It is found the lunar tide in both zonal and meridional winds show significant QBO response, whereas zonal tide only shows significant negative response to solar cycle and positive response to ENSO. Besides, zonal tide only shows significant long-term increasing trend.
Keywords: Lunar tide; Middle atmospheric dynamics; Climatology and planetary waves